FAMILY NURSING CARE USING NUTRITION EDUCATION INTERVENTION ON THE BODY MASS INDEX (BMI) IN SCHOOL-AGE CHILDREN WITH OBESITY IN RT 02 RW 07 KELURAHAN GROGOL KECAMATAN LIMO DEPOK CITY - Anggraini, Nourmayansa Vidya; Pratiwi , Devira Gite (Universitas Airlangga, 2024)
Introduction: The incidence of obesity is continually increasing worldwide, including in both developed and developing countries. This condition can jeopardize health and increase the risk of disabilities in adults. Health education is defined as an effort to provide or improve the understanding, attitude, and actions taken by society in maintaining and improving their health. The purpose of this writing is to evaluate the effectiveness of health education interventions in reducing body mass index (BMI) in school-age children. Method: The implementation method of the intervention is in the form of providing health education to school-age children. In providing health education about obesity in children by eating a diet and consuming healthy foods. Results: The results of the two-week implementation showed that treated patients experienced a decrease in BMI of 0.60 SD, while discharged patients experienced a decrease in BMI of 0.59. It can be concluded that providing health education intervention to school-age children who are obese is an effective measure to reduce their body mass index Conclusion: Therefore, as part of the management of obesity and overweight in school-age children, community nurses are expected to be able to implement health education.